The Expanded Application of Conditional Non-prosecution System in the Era of Petty Crimes - Zhang, Jiayue (International Journal of Social Sciences and Public Administration, 2024)
In response to the new changes in the crime structure under the background of the era of minor offenses, it is necessary to expand and modify China’s current conditional non-prosecution system. Currently, China’s conditional non-prosecution system suffers from narrow scope of application and strict application conditions, making it difficult to achieve the aspirations of non-prosecution in judicial practice, and failing to realize the system’s functions and values. This paper aims to transform the application of the conditional non-prosecution system in the context of minor offenses by addressing its scope of application, additional conditions, and probation periods, and advocates for oversight of its implementation.